Nonlinear fractional arctic systems - Eze, Sunday (Kuwait Journal of Science, 2021)
In this contribution, nonlinear fractional arctic sea-ice model is given and the solution of the model was obtained using a new proposed modified Adomian decomposition method. The result is compared with integer order model and we observed that a model with fractional order gives a better result. We also observed that the effect of climate change on arctic sea-ice could lead to a large scale sea-ice melting with sea level rise for several meters, which could pose a major threat to low-lying island nations and coastal areas.